The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Sintering of Functional Materials 2018
DOI: 10.5772/68082
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Whiteware Body Depending on Different Fluxing Agents and Binders

Abstract: The sintering of whiteware (porcelain) body can be afected by using luxing agents or binders. The chapter describes the sintering process of porcelain body in case of different luxing agent (diferent feldspar rocks, bone ash, zeolite) and binder (kaolin vs. calcium aluminate cement) utilization in the porcelain raw material mixture. Sintering process is presented according to thermodilatometrical curves and sintering temperatures especially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Physical properties i.e. true density, specific surface area, pore diameter and pore volume of raw materials (porcelain and bone china) and commercial hand mold were measured by a gas pycnometer and Ultra-quantachrome, respectively as data tabulated in respectively, close to that of commercial hand mold 2.53 g/cm 3 and consistent with the results by Sokolar [28], Kitouni et al [29] and Toludare et al [30]. Both porcelain and bone china had high specific surface area equal to 13.52 and 10.96 m 2 /g, respectively.…”
Section: Physical and Chemical Properties Of Ceramic Hand Moldssupporting
confidence: 83%
See 1 more Smart Citation
“…Physical properties i.e. true density, specific surface area, pore diameter and pore volume of raw materials (porcelain and bone china) and commercial hand mold were measured by a gas pycnometer and Ultra-quantachrome, respectively as data tabulated in respectively, close to that of commercial hand mold 2.53 g/cm 3 and consistent with the results by Sokolar [28], Kitouni et al [29] and Toludare et al [30]. Both porcelain and bone china had high specific surface area equal to 13.52 and 10.96 m 2 /g, respectively.…”
Section: Physical and Chemical Properties Of Ceramic Hand Moldssupporting
confidence: 83%
“…Furthermore, the viscosity values are important for determining the setting time, draining time for the plaster molds, and the thickness and weight of hand molds after casting. In addition, Sokolar [28], Kitouni et al [29] and Toludare [30] reported using fluxing agents (sintered aids) and binders affected to sintering tempera- 2. If the zeta potential value is in the range ± 10 to ± 30 mV, it means incipient instability and beginning to agglomerate.…”
Section: Physical and Chemical Properties Of Ceramic Hand Moldsmentioning
confidence: 99%
“…Main effect of class C (fluidized) fly ash using in the ceramic mixtures is in the reduction of firing shrinkage of the ceramic body after firing; however, this is at the expense of an increase in porosity of the body and its lower strength -presented in [1]. Addition of FFA in the raw material mixture contributes to a higher porosity of the fired body, especially due to the decomposition of calcium carbonate and anhydride.…”
Section: Results Of Experimentsmentioning
confidence: 99%
“…The studies about the application of FFA in ceramic technology are rare. The fly ash-clay mixtures for the single-firing process technology for the dry pressed ceramic tiles were developed experimentally, using kaolinic stoneware clay as the basic raw material and classic high temperature fly ash [1]. The bodies prepared by this method show a high shrinkage after firing, often even in the reduction cores, in comparison with standard bodies based on natural raw materials.…”
Section: Introductionmentioning
confidence: 99%